Prospects for Security in the Mediterranean - O'Neill, Robert. author. aut Link
VIII, 245 p. 1 illus.
Keywords: A compilation of papers analyzing the issues affecting security in the Mediterranean area and their policy implications. The Mediterranean is seen as a potential theatre for East-West confrontation both on land and at sea, as a key trade route and as an area of inter-relationship conflicts.